A proposed minimum data set for international primary care optometry: a modified Delphi study. (4th May 2017) - Davey, Christopher J.; Slade, Sarah V.; Shickle, Darren
Abstract: Purpose: To identify a minimum list of metrics of international relevance to public health, research and service development which can be extracted from practice management systems and electronic patient records in primary optometric practice. Methods: A two stage modified Delphi technique was used. Stage 1 categorised metrics that may be recorded as being part of a primary eye examination by their importance to research using the results from a previous survey of 40 vision science and public health academics. Delphi stage 2 then gauged the opinion of a panel of seven vision science academics and achieved consensus on contentious metrics and methods of grading/classification. Results: A consensus regarding inclusion and response categories was achieved for nearly all metrics. A recommendation was made of 53 metrics which would be appropriate in a minimum data set. Conclusions: This minimum data set should be easily integrated into clinical practice yet allow vital data to be collected internationally from primary care optometry. It should not be mistaken for a clinical guideline and should not add workload to the optometrist. A pilot study incorporating an additional Delphi stage prior to implementation is advisable to refine some response categories.